Combined two-photon imaging, electrophysiological, and anatomical investigation of the human neocortex in vitro - Kerekes, Bálint Péter (Neurophotonics, 2014)
Spontaneous synchronous population activity (SPA) can be detected by electrophysiological methods in cortical slices of epileptic patients, maintained in a physiological medium in vitro. In order to gain additional spatial information about the network mechanisms involved in the SPA generation, we combined electrophysiological studies with two-photon imaging. Neocortical slices prepared from postoperative tissue of epileptic and tumor patients were maintained in a dual perfusion chamber in a physiological incubation medium. SPA was recorded with a 24-channel extracellular linear microelectrode covering all neocortical layers. After identifying the electrophysiologically active regions of the slice, bolus loading of neuronal and glial markers was applied on the tissue. SPA-related [Formula: see text] transients were detected in a large population of neighboring neurons with two-photon microscopy, simultaneous with extracellular SPA and intracellular whole-cell patch-clamp recordings. The intracellularly recorded cells were filled for subsequent anatomy. The cells were reconstructed in three dimensions and examined with light- and transmission electron microscopy. Combining high spatial resolution two-photon [Formula: see text] imaging techniques and high temporal resolution extra- and intracellular electrophysiology with cellular anatomy may permit a deeper understanding of the structural and functional properties of the human neocortex.